A MULTIMODAL ANALYSIS OF EUROPEAN CAR ADVERTISEMENTS - Dwi Fanti, - (2022)
This study investigates the interactive meaning along with the degree of realness of three Audi car advertisements. The advertisements are in the form of picture, and they are obtained from the Audi official accounts in Instagram, which are @audi as the official global account and @audi_indonesia as the official Indonesia account. For the research design, this study employs a descriptive qualitative method as the study relies on image data. In addition, the study carries out an in-depth analysis of the visual elements within the advertisements. Moreover, in exploring the interactive meanings and the degree of realness of the three advertisements, this study uses Gunther Kress and Theo van Leeuwen's (2006) visual grammar as the theoretical framework. Interestingly, this study reveals that in order to make the audiences see the information offered by the represented participants, Audi tends to make the audiences of their advertisements to feel detached from the advertisements. Moreover, in terms of the degree of realness, it is also revealed that Audi tends to give high value of realness or modality to their advertisements. Furthermore, by conducting this study, hopefully people could become more aware of how the visual elements within an advertisement could project the relation between the producer of the advertisement itself with the audiences.